Relationship of Self-Esteem with Different Domains and Intensities of Habitual Physical Activity in Community-Dwelling Adults - Teixeira, Milena S. [UNESP]; Christofaro, Diego G.D. [UNESP]; Delfino, Leandro D. [UNESP]; Saraiva, Bruna T.C. [UNESP]; Santos, Amanda B. [UNESP]; Leite, Enrique G.F. [UNESP]; Gonzales, Kathryn; Ferrari, Gerson; Lofrano-Prado, Mara C.; Tebar, William R. [UNESP] (Wolters Kluwer, 2025)
Introduction Self-esteem has been positively associated with physical activity, but it is not clear whether different domains and intensities of physical activity are differently related to self-esteem in community-dwelling adults. This study aimed to analyze the relationship between self-esteem and different domains and intensities of physical activity in adults. Methods This cross-sectional study included a randomly selected sample of 252 community-dwelling adults (mean age: 42.6 ± 17.2 yr), of whom 58.8% were female. Self-esteem and physical activity domains (occupational physical activity, exercise and sports in leisure, and leisure and commuting physical activity) were assessed using questionnaires, and physical activity intensities were objectively measured using accelerometry. Age, sex, socioeconomic status, and body mass index were adopted as covariates. Results Self-esteem scores were positively associated with occupational physical activity (β = 1.29; 95% confidence interval (CI), 0.17-2.40) and exercise and sports in leisure (β = 0.81; 95% CI, 0.14-1.49). Being physically active in at least one physical activity domain was associated with 88% lower odds of presenting low self-esteem (odds ratio, 0.12; 95% CI, 0.02-0.80). Conclusion Self-esteem was cross-sectionally associated with both occupational and exercise/sports physical activity, as well as with being physically active in at least one physical activity domain. Efforts to promote mental health in community-dwelling adults should consider domain-specific physical activity, regardless of physical activity intensity.